2005
DOI: 10.1007/s11060-004-4204-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Enhanced Vascular Endothelial Growth Factor (VEGF) Secretion in Glioblastoma Multiforme Cell Lines – A Clue to Radioresistance?

Abstract: Irradiation enhanced VEGF secretion in all three tested glioma cell lines (up to eight times basal levels). It is tempting to associate the radiation-enhanced VEGF secretion with an increased angiogenic potential of the tumor, which may be a factor in radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 15 publications
7
53
1
Order By: Relevance
“…It is also suggested that the expression of VEGF in tumors is up-regulated after radiotherapy, which is thought to be a defense mechanism against radiation (Hovinga et al 2005). Consistently, cancers with overexpressed VEGF are insensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…It is also suggested that the expression of VEGF in tumors is up-regulated after radiotherapy, which is thought to be a defense mechanism against radiation (Hovinga et al 2005). Consistently, cancers with overexpressed VEGF are insensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies (3,4) have indicated that radiation therapy results in the elevated expression of vascular endothelial growth factor (VEGF), which may contribute to the resistance to radiation in tumors. Therefore, radiation therapy combined with antiangiogenic therapy may be effective in decreasing radiation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the biological impact of VEGF stimulation on human GBM cell models, we treated the cell lines A172 and U251MG with increasing concentrations of VEGF (10,20,40 and 80 ng/ ml) and measured MTT absorbance in time-course experiments, as an index of cell growth/proliferation, as employed in previous studies of VEGF-induced astrocytoma cell proliferation. [15][16][17][18] As early as 6-12 hours after addition of VEGF 121 to culture medium, MTT absorbance was significantly increased (by 19-35% for A172 and 14-79% for U251MG, p < 0.001 for any of the four VEGF concentrations used) compared with the mock-treated control cells. Despite some modestly higher increases of MTT absorbance at the higher versus lower concentrations of added VEGF, such concentration-dependence was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%